OCTA measurements in Behcet’s disease across different stages of the disease activity: A systematic review and meta-analysis - Mehrdad Mozafar; Mobina Amanollahi; Reza Samiee; Melika Jameie; Ali Mousavi; Zahra Ghanbari; Helia Nafar; Negar Mozafar; Fatemeh Amiri; Mehdi Azizmohammad Looha; Elias Khalili Pour; Nazanin Ebrahimiadib (PLoS ONE, 2025)
Purpose Behcet disease (BD) is an autoimmune disease characterized by diffuse all-sized obliterative vasculitis, thrombotic vasculopathy, and common ocular involvement. This study aims to evaluate the retinal microvascular alterations in BD using optical coherence tomography angiography (OCTA). Methods PubMed, Embase, and Web of Sciences were systematically searched for relevant studies assessing OCTA measurements in BD and healthy controls (HCs). Meta-analysis was conducted on OCTA parameters with at least two studies using the same OCTA device, with similar case and control groups. A qualitative synthesis approach was used to report the data that could not be pooled. Results Twenty-eight related studies (769 BD subjects, 123 active BU eyes, 462 inactive BU eyes, 112 non-specified ocular BD, and 486 non-ocular BD eyes) were included. Patients with inactive Behcet uveitis (BU) and non-ocular BD showed a statistically significant greater FAZ size and lower superficial retinal capillary plexus and deep retinal capillary plexus vessel density (VD) in comparison to HCs, particularly in the parafoveal sector. Also, radial peripapillary capillary (RPC) VD was lower in patients with inactive BU than HCs. However, no significant difference in OCTA parameters was found in patients with active BU compared to HCs. Conclusions Meta-analysis demonstrated reduced VD in various regions and greater FAZ size in superficial and deep retinal plexuses, particularly in inactive BU and non-ocular BD, which are mostly studied so far. However, more studies with larger sample sizes should draw a more definite conclusion. OCTA can provide valuable insights into retinal microvasculature changes in BD.